Role of Subcutaneous Negative Suction versus Simple Subcutaneous Drain Closure in Contaminated Abdominal Surgeries in Pediatric Age Group - Imtiaz Ahmed, Iqra Aslam, Ghashia Khan, Muhammad Akbar, Ali Hasham, Muhammad Anwar Memon (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Contaminated abdominal surgical laparotomy incisions and their care are basic principles in the field of surgery. In emergency or trauma laparotomy, the primary surgeon’s pivotal role is to optimize the untoward incision wound response, excise or debride viable/nonviable tissues, and alleviate the process of wound healing near to normal function. In contaminated abdominal surgeries, wound contamination is unavoidable that occurs at the time of surgery, and several methods are used to prevent wound complications. Material and Methods: To assess the impact of subcutaneous negative suction versus simple subcutaneous drains on the outcome of surgical wound infection, we conducted an observational study involving patients with contaminated abdominal surgical laparotomy wounds. The study was conducted in the Department of Pediatric Surgery at Liaquat University Hospital Hyderabad. Over five years from January 2015 to December 2020 about 300 patients underwent emergency or trauma laparotomy. Patients were divided into two groups A and B 150 each group by random sampling. Results: In our study, negative suction drain versus simple subcutaneous drain without suction during the closure of the contaminated abdominal surgical wound in emergency or trauma laparotomy, the negative suction drain is highly suggestive to decrease postoperative wound infection, seroma formation, and wound disruption. Compared to a simple subcutaneous drain, the utilization of a subcutaneous suction drain following the closure of the abdominal sheath result in effective wound drainage, reducing the risk of wound infection and disruption. Conclusion: Subcutaneous suction drain has a better outcome as compared with simple subcutaneous without suction in the management of contaminated surgical laparotomy wounds. Keywords: Negative suction drain, simple drain, seroma, wound disruption.